The Relationship between Sexual Function and Quality of Life in Cervical Cancer Patients - Rinda Intan Sari; Anis Ardiyanti; Nella Vallen Ika Puspita (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Introduction: Patients with cervical cancer have various physical complaints that can be felt directly, one of which is impaired sexual function, hormonal changes that occur due to the course of cervical cancer can cause decreased sexual desire, decreased lubrication and dyspareunia. Sexual function can result in decreased quality of life for women as an important role in sexuality. Many studies focus on the quality of life, but have not revealed sexual function. Objectives: The purpose of this study was to analyze the relationship between sexual function and quality of life for cervical cancer patients. Methods: Quantitative research design using cross-sectional method. Sample selection using quota sampling technique with 60 respondents. The instruments in this study were FSFI and WHOQoL. Data processing and analysis using the SPSS program with Spearman-rank test. Results: The majority of respondents were adults (81.7%) and underwent multitherapy (73.3%). A total of 53 respondents experienced sexual dysfunction and 55 respondents had a good quality of life. The results of the Spearman rank statistical test showed that the p-value was 0.030 (<0.05). It can be concluded that there is a relationship between sexual function and quality of life and has a weak relationship strength. Conclusions: Sexual function is a factor related to the quality of life of cervical cancer patients. Therefore, nurses must be able to reveal the sexual function experienced by patients in providing more comprehensive nursing care so that they can improve their quality of life.